Health inequalities on settlement level by the triadic resolution of economic development - Egri, Zoltán (Studia Mundi – Economica, 2017)
The aim of our study is to introduce the health inequalities relating to the economical development at the level of Hungarian settlements. I used the method of the triadic resolution of the economic development to get my goal and in conclusion, with the help of this method I could show that the certain development categories and the health condition are paralel to each other. My results were validated with mathematical-statistical methods (Spearman’s rank correlation, Kruskal Wallis H test) as well.